Can difference make a difference? A critical theory discussion of religion in sexuality education. Issue 3 (4th May 2018) - Sanjakdar, Fida
ABSTRACT: This article conceptualizes religion as a critical theory challenge to sexuality education. Religious views in sexuality education are often perceived as intolerant and incompatible with today's progressive and modern society. This article engages with the idea that the inclusion of religious viewpoints on sexuality will challenge the efficacy of current sexuality education in Australia and New Zealand school contexts, to create a more contemporary and inclusive learning experience that caters for all students' sexual needs and lives. Utilizing a critical theory lens, I demonstrate how religion can challenge dominant views of sexuality education, introduce alternative modes of content and delivering, promote critical thinking skills and more egalitarian ways of learning about sexuality. Drawing on data collected from Australian and New Zealand public schools, this article endeavors to reframe current discussions of the relationships between religion and sexuality education.